ABOUT THE ORGANIZATION OF THE LEGAL FOUNDATIONS OF THE NEW EDITION OF THE UKRAINIAN AIR CODE - Baran, R. T.; Baran, L. M.; Mihdal, Ye. V. (Science and Transport Progress, 2009)
The authors’ own scientific and practical approaches to the issuing of the clauses of new Air Code of Ukraine are proposed. There are presented the conceptual basics of organization and legal regulation of the legislative instructions, which especially concern to the chapters regarding regulation of the conditions and order of use of the air space of Ukraine, organizational and economic aspects of activities of airports etc. The models of structuring the organizational subsystems for the commercial and state sectors of the air space and the forms of the organizationalandmanagerial structures, managerial methods and economical airport systems are also proposed.